Gate Tunable In‐ and Out‐of‐Plane Spin–Orbit Coupling and Spin‐Splitting Anisotropy at LaAlO3/SrTiO3 (110) Interface. (10th June 2015) - Gopinadhan, Kalon; Annadi, Anil; Kim, Younghyun; Srivastava, Amar; Kumar, Brijesh; Chen, Jingsheng; Coey, J. Michael D.; Ariando; Venkatesan, Thirumalai
<x xml:space="preserve">Abstract</x> Manipulating spin–orbit coupling (SOC) is important for devices such as spin–orbit torque‐based memory and its understanding is necessary to answer several fundamental open questions in triplet state superconductivity, topological insulators, and Majorana fermions. Here spin splitting of 25 meV is reported at the LaAlO3/SrTiO3 (110) interface for in‐plane spins at a current density of 1.4 × 104 A cm−2, which is large compared to that found in semiconductor heterostructures or the LaAlO3/SrTiO3 (100) interface, and in addition it is anisotropic. The anisotropy arises from the difference in electron effective mass along the [001] and [1–10] directions. Our study predicts a spin‐splitting energy >1000 meV at a current density of 107 A cm−2, which is enormous compared to metallic systems and will be an ideal spin‐polarized source. In addition to the in‐plane effect, there is an unexpected gate‐tunable out‐of‐plane SOC at the LaAlO3/SrTiO3 (110) interface when the spins lie out‐of‐plane due to broken symmetry in the plane of the interface. It is demonstrated that this can be manipulated by varying the LaAlO3 thickness showing that this interface can be engineered for spin–orbit torque devices.